Peningkatan Kualitas Pembelajaran Pengenalan Organ Tubuh Manusia Menggunakan Aplikasi Wordwall di TK Pembina - Nanda S Prawira; Inda Anggraini (PPPM Institut Teknologi Pagar Alam, 2025)
Early childhood education serves as a fundamental stage in developing children’s cognitive abilities and basic conceptual understanding. One essential learning material introduced at this level is the recognition of human body parts and organs. However, preliminary observations at TK Pembina Kota Pagar Alam revealed that learning activities were predominantly conducted using conventional methods, resulting in low student engagement and suboptimal learning outcomes. This condition highlights the need for innovative and interactive learning media that align with the characteristics of early childhood learners.This study aims to improve the quality of learning on the recognition of human body parts and organs through the utilization of the Wordwall application. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Interactive learning media were designed in the form of game-based activities using Wordwall and implemented in classroom learning.The findings indicate a notable improvement in students’ learning outcomes after the implementation of the Wordwall-based learning media. The average student score increased from 65 prior to the intervention to 83 after implementation. Additionally, improvements were observed in students’ activeness and learning enthusiasm, indicating higher engagement during the learning process. The results demonstrate that the use of Wordwall contributes positively to creating an interactive, enjoyable, and effective learning environment. In conclusion, the Wordwall application is proven to be an effective digital learning medium for enhancing the quality of early childhood education, particularly in learning about human body parts and organs. This study provides practical implications for educators in integrating technology-based learning media into early childhood classrooms.